An Important Role of Portfolio Assessment in Indonesian EFL Writing Learning Contexts - Kristian Wijaya (Institut Agama Islam Negeri Madura, 2022)
Abstract: To intensively solidify Indonesian EFL learners’ writing competencies development, teachers need to constantly internalize portfolio assessment in their daily-based writing teaching-learning dynamics. This current small-scale library study aimed to profoundly investigate an important role of portfolio assessment in Indonesian EFL writing learning contexts. Concerning this major research objectivity, the researcher conscientiously selected 30 prior journal articles overviewing this main theme in this archipelago starting from 2015 until 2021 year to yield more relevant research findings in nowadays second language writing learning contexts. This current small-scale qualitative investigation was conducted in the support of library study approach in order to obtain more robust research findings relevant to the portfolio assessment implemented in Indonesian EFL learning contexts. He obtained research results revealed: (1) The proper utilization of portfolio assessment can arm learners with advanced writing competencies and (2) The continual integration of portfolio assessment can promote more holistic writing learning outcomes. As an eventual remark, it can be inferred that the incorporation of portfolio assessment is critically pivotal not merely for developing Indonesian EFL learners’ writing proficiency to the utmost levels but also for supportive writing behaviors while engaging in varied complex writing learning enterprises